Laboratory evaluation of the (VIS, IR) scattering matrix of complex-shaped ragweed pollen particles. (October 2020) - Cholleton, Danaël; Bialic, Emilie; Dumas, Antoine; Kaluzny, Pascal; Rairoux, Patrick; Miffre, Alain
Highlights: Light scattering by complex-shaped large particles is investigated in laboratory. The scattering matrix of airborne ragweed pollen is measured as a case study. A (VIS, IR) polarimeter has hence been built and validated on spherical particles. The (VIS, IR) spectral dependence of the ragweed scattering matrix is revealed. Abstract: Ragweed or Ambrosia artemisiifolia pollen is an important atmospheric constituent affecting the Earth's climate and public health. The literature on light scattering by pollens embedded in ambient air is however rather sparse: polarization measurements are limited to the sole depolarization ratio and pollens are beyond the reach of numerically exact light scattering models mainly due to their tens of micrometre size. Also, ragweed pollen presents a very complex shape, with a small-scale external structure exhibiting spikes that bears some resemblance with coronavirus, but also apertures and micrometre holes. In this paper, to face such a complexity, a controlled-laboratory experiment is proposed to evaluate the scattering matrix of ragweed pollen embedded in ambient air. It is based on a newly-built polarimeter, operating in the infra-red spectral range, to account for the large size of ragweed pollen. Moreover, the ragweed scattering matrix is also evaluated in the visible spectral range to reveal the spectral dependence of the ragweed scattering matrix within experimental error bars. As an output, precise spectral and polarimetric fingerprints for large size and complex-shaped ragweed pollen particles are then provided. We believe our laboratory experiment may interest the light scattering community by complementing other light scattering experiments and proposing outlooks for numerical work on large and complex-shaped particles.